Konstruksi Miteme dalam Cerita Rakyat Sumbawa “Paruma Ero”: Kajian Strukturalisme Perspektif Levi-Strauss - Eirzikri Rentarimasa; Mahsun; Johan Mahyudi (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2023)
This research aims to describe the myteme and structures of the Sumbawa Paruma Ero folklore level based on Levi Strauss structuralism of research. This research used a qualitative description methods with a structural approach. Methods of collecting data using library methods and note-taking techniques. Levi - Strauss structuralism theory as the basis of his analysis. The results of the analysis of the mytemes in the Sumbawa Paruma Ero folklore are divided into six mytemes: (1) The myteme of the stories Lalu Muhammad Maula paying attention to the take a bath of Bidadari, (2) The myteme of the story the Bidadari Married, (3) The myteme of loyalty and lying, (4) The myteme of the birth of a child then Muhammad Maula, (5) Myteme the story of the departure of the angel and then Muhammad Maula flew, (6) The mytee of the story revealed by Paruma Ero. The structures of the levels in the Paruma Ero stories is divided into four levels: (1) the geographical level, namely the level related to the setting of the place in the stories, (2) the techno-economic level, namely the level related to livelihoods, (3) the sociological level concerning the social life involved. bind the characters, (4) the cosmological level concerns the supernatural things experienced by the characters in the stories